Homozygous loss‐of‐function variants of TASP1, a gene encoding an activator of the histone methyltransferases KMT2A and KMT2D, cause a syndrome of developmental delay, happy demeanor, distinctive facial features, and congenital anomalies. Issue 11 (22nd July 2019) - Suleiman, Jehan; Riedhammer, Korbinian M.; Jicinsky, Timothy; Mundt, Melinda; Werner, Laurie; Gusic, Mirjana; Burgemeister, Anna L.; Alsaif, Hessa S.; Abdulrahim, Maha; Moghrabi, Nabil N; Nicolas‐Jilwan, Manal; AlSayed, Moeenaldeen; et al.
Abstract: We report four unrelated children with homozygous loss‐of‐function variants in TASP1 and an overlapping phenotype comprising developmental delay with hypotonia and microcephaly, feeding difficulties with failure‐to‐thrive, recurrent respiratory infections, cardiovascular malformations, cryptorchidism, happy demeanor, and distinctive facial features. Two children had a homozygous founder deletion encompassing exons 5–11 of TASP1, the third had a homozygous missense variant, c.701 C>T (p.Thr234Met), affecting the active site of the encoded enzyme, and the fourth had a homozygous nonsense variant, c.199 C>T (p.Arg67*). TASP1 encodes taspase 1 (TASP1), which is responsible for cleaving, thus activating, the lysine methyltransferases KMT2A and KMT2D, which are essential for histone methylation and transcription regulation. The consistency of the phenotype, the critical biological function of TASP1, the deleterious nature of the TASP1 variants, and the overlapping features with Wiedemann–Steiner and Kabuki syndromes respectively caused by pathogenic variants in KMT2A and KMT2D all support that TASP1 is a disease‐related gene.